PACAP, VIP and their receptors in the metazoa Insights about the origin and evolution of the ligand-receptor pair - Cardoso, J. C. R. (2014)
The evolution, function and interaction of ligand–receptor pairs are of major pharmaceutical interest. Comparative sequence analysis approaches using data from phylogenetically distant organisms can provide insights into their origin and possible physiological roles. The present review focuses on the pituitary adenylate cyclase-activating polypeptide (PACAP), vasoactive intestinal polypeptide (VIP) and their receptors in the metazoa. A PACAP-like peptide is present in tunicates and chordates while VIP- and PACAP/VIP-specific receptors have only been isolated in the latter phyla. The apparently disparate evolution of the ligands and their specific receptors raises questions about their evolution during the metazoan radiation and also about how the ligands may have acquired new functions.